Preparation method of positive electrode material, positive electrode and battery

By using airflow milling to treat the mixture of single crystal lithium manganese oxide and polymer powder when preparing the positive electrode material, and forming a carbon layer coating at high temperature, the agglomeration and uniformity problems in the traditional coating process are solved, and the conductivity of the material and the cycling performance of the battery are improved.

CN119674019APending Publication Date: 2025-03-21QINGTAO (KUNSHAN) ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411891188.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The traditional method of preparing the coating layer is difficult to effectively prevent the agglomeration of single crystal lithium manganese oxide, resulting in weakening the manganese dissolution effect. At the same time, the wet process cost is high, the dry process coating thickness is difficult to control, and the uniformity is poor.

Method used

The mixture of single crystal lithium manganese oxide and polymer powder is treated by airflow grinding to dissociate and disperse, the polymer fibrosis and encapsulates the surface of lithium manganese oxide, and then high-temperature treatment is carried out under the protection of inert gas to form a lithium manganese oxide material with a carbon layer on the surface.

Benefits of technology

The uniform coating of single crystal lithium manganese oxide is achieved, which improves the conductivity of the material, reduces the polarization of the battery, and improves the circulation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674019A_ABST
    Figure CN119674019A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a positive electrode material, a positive electrode and a battery. The preparation method of the positive electrode material comprises the following steps: S1, mixing single-crystal lithium manganate and polymer powder to prepare a mixture; s2, the mixture is put into an airflow mill to be treated, and an intermediate is prepared; s3, under the protection of inert gas, performing high-temperature treatment on the intermediate to prepare a lithium manganate material coated with a carbon layer on the surface, namely the positive electrode material; wherein the polymer powder is fiberizable polymer powder; the high-temperature treatment temperature is T1, the carbonization temperature of the polymer powder is T2, and T1 is larger than or equal to T2. According to the preparation method disclosed by the invention, a coating method of fibration and carbonization of the polymer powder is adopted, so that a coating layer is more uniform, the conductivity of the lithium manganate material is improved, the battery polarization is reduced, and the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a method for preparing a positive electrode material, a positive electrode, and a battery. Background Art

[0002] As a positive electrode material, lithium manganese oxide has attracted extensive attention due to its high charge and discharge voltage platform, excellent rate performance, and low cost. However, in actual use, manganese is easily dissolved when lithium manganese oxide comes into contact with the electrolyte, resulting in a rapid capacity decay of lithium-ion batteries. Therefore, coating is often used to isolate the contact between the electrolyte and lithium manganese oxide. On the other hand, lithium manganese oxide is divided into single-crystal lithium manganese oxide and polycrystalline lithium manganese oxide. Compared with polycrystalline lithium manganese oxide, single-crystal lithium manganese oxide has a smaller specific surface area, which is beneficial to reduce contact with the electrolyte and improve manganese dissolution. Therefore, single-crystal lithium manganese oxide is often selected as the source of raw materials.

[0003] The traditional methods for preparing coating layers are mainly wet coating and dry coating. The coating effect of wet coating is more uniform. However, during the coating process, single crystal lithium manganese oxide is prone to agglomeration, resulting in a weakened effect of inhibiting manganese dissolution. In addition, the wet process is more expensive and less practical. Dry coating is more practical, but the coating thickness is difficult to control, often forming an island-shaped coating layer, and uniformity is difficult to ensure.

[0004] Therefore, there is an urgent need for a coating process that can effectively prevent the agglomeration of single-crystal lithium manganese oxide and form a uniform coating layer. Summary of the invention

[0005] Based on this, the present application provides a method for preparing a positive electrode material, a positive electrode, and a battery to solve the above technical problems.

[0006] The first aspect of the present application provides a method for preparing a positive electrode material, comprising the following steps:

[0007] S1, mixing single crystal lithium manganese oxide and polymer powder to prepare a mixture;

[0008] S2, placing the mixed material into a jet mill for processing to obtain an intermediate;

[0009] S3. Under the protection of an inert gas, the intermediate is subjected to high temperature treatment to obtain a lithium manganese oxide material having a carbon layer coated on the surface, i.e., a positive electrode material;

[0010] Wherein, the polymer powder is a fiberizable polymer powder;

[0011] The temperature of the high temperature treatment is T1, the carbonization temperature of the polymer powder is T2, and T1≥T2.

[0012] In some embodiments, the type of polymer powder includes at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene (PE), and polypropylene (PP).

[0013] In some embodiments, in the above-mentioned mixture, the mass ratio of the polymer powder to the single crystal lithium manganese oxide is 500ppm to 10000ppm.

[0014] In some embodiments, in the above-mentioned mixture, the mass ratio of the polymer powder to the single crystal lithium manganese oxide is 2000ppm to 3000ppm.

[0015] In some embodiments, the feeding frequency of the jet mill is 8 Hz to 12 Hz.

[0016] In some embodiments, the classification frequency of the jet mill is 20 Hz to 30 Hz.

[0017] In some embodiments, the fan frequency of the jet mill is 40 Hz to 50 Hz.

[0018] In some embodiments, the high temperature treatment time is 6 h to 10 h.

[0019] In some embodiments, the inert gas is at least one of nitrogen, helium, and argon.

[0020] In some embodiments, the carbon layer has a thickness of 1 nm to 30 nm.

[0021] A second aspect of the present application provides a positive electrode, which includes a positive electrode material prepared according to the method for preparing a positive electrode material provided in the first aspect.

[0022] In some embodiments, the positive electrode further includes a binder and a conductive agent.

[0023] A third aspect of the present application provides a battery, which includes the positive electrode provided in the second aspect.

[0024] In the present application, before high temperature treatment, the mixture of single crystal lithium manganese oxide and polymer powder is placed in a jet mill for treatment, so that the single crystal lithium manganese oxide is dissociated and dispersed and transformed into a granular structure. At the same time, the polymer is transformed from powder into fiber and wrapped on the surface of the single crystal lithium manganese oxide to prevent the single crystal lithium manganese oxide from aggregating again. The coating method of fiberizing the polymer powder and then carbonizing it makes the coating layer more uniform, improves the conductivity of the lithium manganese oxide material, reduces the polarization of the battery, and improves the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more completely understand the present application and its beneficial effects, the following description will be given in conjunction with the accompanying drawings. In the following description, the same reference numerals represent the same parts.

[0026] Figure 1 This is a flow chart of a method for preparing a positive electrode material in one embodiment of the present application. DETAILED DESCRIPTION

[0027] References to embodiments of the present application will now be provided in detail, one or more embodiments of which are described below. Each embodiment is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0028] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0029] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0030] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0031] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 100~150nm means that the units of the left endpoint "100" and the right endpoint "150" are both nm (nanometers).

[0032] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0033] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0034] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, mentioning that the method may also include step (c) means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0035] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0036] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0037] like Figure 1 As shown, the first aspect of the present application provides a method for preparing a positive electrode material, comprising the following steps:

[0038] S1. Mixing single crystal lithium manganese oxide and polymer powder to prepare a mixture.

[0039] S2. The mixed material is placed in a jet mill for processing to obtain an intermediate.

[0040] S3. Under the protection of an inert gas, the intermediate is subjected to high-temperature treatment to obtain a lithium manganese oxide material having a surface coated with a carbon layer, i.e., a positive electrode material.

[0041] Wherein, in the above step S1, the polymer powder used is a fiberizable polymer powder.

[0042] In the above step S3, the temperature of the high temperature treatment is T1, the carbonization temperature of the polymer powder is T2, and T1≥T2.

[0043] In some embodiments, the type of polymer powder includes at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene (PE), and polypropylene (PP).

[0044] Exemplarily, when polytetrafluoroethylene (PTFE) is selected as the polymer, the carbonization temperature T2 of polytetrafluoroethylene (PTFE) is 400°C. At this time, the temperature T1 of the high temperature treatment is ≥400°C, including but not limited to 400°C, 450°C, 500°C, 550°C, and 600°C.

[0045] In some embodiments, in the mixture of step S1 above, the mass ratio of polymer powder to single crystal lithium manganate is 500ppm to 10000ppm, including but not limited to 500ppm, 1000ppm, 2000ppm, 3000ppm, 4000ppm, 5000ppm, 6000ppm, 7000ppm, 8000ppm, 9000ppm, 10000ppm. If the mass ratio is too large, the thickness of the coating layer increases, which is not conducive to the transmission of lithium ions and the improvement of the energy density of the battery. If the mass ratio is too small, a complete and continuous coating cannot be formed on the surface of the single crystal lithium manganate particles, and the effect improvement is limited.

[0046] In some embodiments, in the above-mentioned mixture, the mass ratio of polymer powder to single crystal lithium manganese oxide is 2000ppm to 3000ppm, including but not limited to 2000ppm, 2100ppm, 2200ppm, 2300ppm, 2400ppm, 2500ppm, 2600ppm, 2700ppm, 2800ppm, 2900ppm, and 3000ppm.

[0047] In some embodiments, the feeding frequency of the jet mill is 8 Hz to 12 Hz, including but not limited to 8 Hz, 9 Hz, 10 Hz, 11 Hz, and 12 Hz.

[0048] In some embodiments, the classification frequency of the jet mill is 20 Hz to 30 Hz, including but not limited to 20 Hz, 22 Hz, 24 Hz, 26 Hz, 28 Hz, and 30 Hz.

[0049] In some embodiments, the fan frequency of the jet mill is 40 Hz to 50 Hz, including but not limited to 40 Hz, 42 Hz, 44 Hz, 46 Hz, 48 Hz, and 50 Hz.

[0050] In some embodiments, the high temperature treatment time is 6 h to 10 h, including but not limited to 6 h, 6.5 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 9.5 h, and 10 h.

[0051] In some embodiments, the inert gas is at least one of nitrogen, helium, and argon.

[0052] In some embodiments, the thickness of the carbon layer is 1 nm to 30 nm, including but not limited to 1 nm, 3 nm, 5 nm, 7 nm, 10 nm, 12 nm, 15 nm, 20 nm, 22 nm, 25 nm, and 30 nm.

[0053] In the present application, before high temperature treatment, the mixture of single crystal lithium manganese oxide and polymer powder is placed in a jet mill for treatment, so that the single crystal lithium manganese oxide is dissociated and dispersed and transformed into a granular structure. At the same time, the polymer is transformed from powder into fiber and wrapped on the surface of the single crystal lithium manganese oxide to prevent the single crystal lithium manganese oxide from aggregating again. The coating method of fiberizing the polymer powder and then carbonizing it makes the coating layer more uniform, improves the conductivity of the lithium manganese oxide material, reduces the polarization of the battery, and improves the cycle performance of the battery.

[0054] A second aspect of the present application provides a positive electrode, which includes a positive electrode material prepared according to the method for preparing a positive electrode material provided in the first aspect.

[0055] In some embodiments, the positive electrode further includes a binder, a conductive agent, and a positive electrode current collector.

[0056] It is understood that the present application has no particular restrictions on the positive electrode current collector, as long as it has conductivity and does not cause chemical changes in the battery. Specifically, copper, stainless steel, aluminum, nickel, titanium, or a metal current collector with a surface treated with carbon or other substances can be used.

[0057] The binder in the positive electrode is mainly used to bind the positive electrode material, the conductive agent, the positive electrode current collector and other components together. The binder includes, but is not limited to, one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), polyoxymethylene (POM), polycarbonate (PC), polyamide (PA), acrylic plastics, other polyolefins and their copolymers, polysulfone, polyphenylene oxide (PPO) and carboxymethyl cellulose (CMC).

[0058] The conductive agent in the positive electrode is mainly used to assist and improve the conductivity in the battery, and there is no particular limitation on it in the present application, as long as it has conductivity without causing chemical changes. Specifically, the conductive agent may include graphite, such as natural graphite or artificial graphite; carbon materials, such as conductive carbon black (super-P), acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; metal powders, such as fluorocarbon powders, aluminum powders, and nickel powders; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives, and from the aspect of improving conductivity, the conductive agent may preferably be carbon black.

[0059] In some embodiments, the positive electrode may be manufactured by coating a positive electrode slurry on a positive electrode collector, followed by drying and roll-pressing, wherein the positive electrode slurry includes a solvent and a positive electrode material and / or a binder and / or a conductive agent dissolved in the solvent.

[0060] The solvent may include an organic solvent, such as N-methyl-2-pyrrolidone (NMP), and may be used in an amount such that a preferred viscosity is obtained when the positive electrode material is included and optionally a binder, a conductive agent, etc. For example, the amount of the solvent included in the positive electrode slurry may be such that the concentration of the solids including the positive electrode material and optionally a binder and a conductive agent is 50 wt % to 95 wt %, preferably 70 wt % to 90 wt %.

[0061] In some of the embodiments, the positive electrode can be prepared by a dry method, that is, the positive electrode material, the conductive agent, and the binder are mixed, or the positive electrode material and the conductive agent are first mixed, and then the binder is added. Under the action of high shear force, the binder is converted from a powder state to a fibrous state to bind the positive electrode material and the conductive agent together, and the positive electrode active layer is formed by rolling. Finally, the positive electrode active layer and the positive electrode current collector are rolled and compounded to obtain the positive electrode.

[0062] In some embodiments, the mass proportion of the positive electrode material in the positive electrode active layer is 85wt%-99wt%, preferably 90wt%-98wt%, and more preferably 95wt%-98wt%.

[0063] In some embodiments, the mass proportion of the binder in the positive electrode active layer is 1 wt %-10 wt %, preferably 1 wt %-5 wt %, and more preferably 2 wt %-3 wt %.

[0064] A third aspect of the present application provides a battery, which includes the positive electrode provided in the second aspect.

[0065] In some embodiments, the battery further includes a negative electrode.

[0066] It is understood that in the present application, there is no particular limitation on the negative electrode, as long as it can function as the negative electrode of the battery under the premise of conforming to the overall inventive concept of the present application. The following is only exemplary, and the negative electrode includes a negative electrode current collector, a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder.

[0067] In some embodiments, the shape of the negative electrode current collector includes any one of a foil shape, a plate shape, or a mesh shape.

[0068] Furthermore, the negative electrode current collector includes but is not limited to any one of aluminum, copper, nickel or zinc; optionally, the negative electrode current collector is copper, such as copper foil.

[0069] Furthermore, the negative electrode current collector includes any one of aluminum, copper, nickel or zinc alloy.

[0070] In some embodiments, the negative electrode active material includes, but is not limited to, one or more of graphite, silicon, silicon oxygen, silicon carbon, lithium titanate, hard carbon, soft carbon, tin oxide, and titanium dioxide materials.

[0071] In some embodiments, the negative electrode conductive agent includes, but is not limited to, carbon-based materials, powdered nickel or other metal particles or conductive polymers. Carbon-based materials may include, for example, particles of carbon black, graphite, super-P, acetylene black (such as KETCHENTM black or DENKATM black), carbon fibers and nanotubes, graphene, etc. Examples of conductive polymers include polyaniline, polythiophene, polyacetylene, polypyrrole, poly (3,4-ethylenedioxythiophene) polystyrene sulfonate, and the like.

[0072] In some embodiments, the negative electrode binder includes but is not limited to one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), polyoxymethylene (POM), polycarbonate (PC), polyamide (PA), acrylic plastics, other polyolefins and copolymers thereof, polysulfone, polyphenylene ether (PPO), carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR).

[0073] In some embodiments, the negative electrode active material, the negative electrode conductive agent and the negative electrode binder together constitute a negative electrode active layer. The negative electrode active layer is disposed on the surface of the positive electrode current collector to obtain a negative electrode.

[0074] In some embodiments, in the negative electrode active layer, the negative electrode active material accounts for 85 wt % to 99 wt %, preferably 90 wt % to 99 wt %, and particularly preferably 95 wt % to 98 wt %.

[0075] In some embodiments, the mass proportion of the negative electrode conductive agent in the negative electrode active layer is 0.5wt%-10wt%, preferably 1wt%-5wt%, and more preferably 1wt%-3wt%.

[0076] In some embodiments, the battery further includes an electrolyte.

[0077] It is understandable that in the present application, there is no particular limitation on the electrolyte in the battery, and any known electrolyte that can be used to prepare a battery can be applied to the present application without violating the inventive concept of the present application.

[0078] It can also be understood that the method for preparing the battery is not particularly limited in the present application, and any known process method for preparing the battery can be applied to the present application without violating the inventive concept of the present application.

[0079] The present application will be further described below with reference to specific embodiments and comparative examples.

[0080] Example 1

[0081] Preparation of positive electrode materials:

[0082] S1. Mixing single crystal lithium manganese oxide and polymer powder to prepare a mixture.

[0083] The polymer powder is polytetrafluoroethylene (PTFE) powder; and the mass ratio of the polymer powder to single crystal lithium manganese oxide is 2000ppm.

[0084] S2. The mixed material is placed in a jet mill for processing to obtain an intermediate.

[0085] Among them, the feeding frequency of the air jet mill is 10Hz, the classification frequency is 25Hz, and the fan frequency is 45Hz.

[0086] S3. Under the protection of an inert gas, the intermediate is subjected to high-temperature treatment to obtain a lithium manganese oxide material having a surface coated with a carbon layer, i.e., a positive electrode material.

[0087] The inert gas is argon, the high temperature treatment temperature is 400°C, the high temperature treatment time is 8 hours, and the thickness of the carbon layer is 5 nm.

[0088] Positive electrode: The positive electrode slurry (the mass ratio of the positive electrode material, binder (PVDF) and conductive agent (super-P) prepared above is 95:3:2) is coated on aluminum foil, dried and roll-pressed to obtain the positive electrode.

[0089] Negative electrode: The negative electrode slurry (the mass ratio of graphite, binder (CMC+SBR) and conductive agent (super-P) is 95:3:2) is coated on copper foil, dried and roll-pressed to obtain the negative electrode.

[0090] The mass ratio of electrolyte: ethylene carbonate (EC): propylene carbonate (PC): diethyl carbonate (DEC): lithium hexafluorophosphate (LiPF6) is 35:28:23:14.

[0091] Diaphragm (PE film, homemade).

[0092] Preparation of batteries

[0093] The positive electrode, the negative electrode and the separator are wound / stacked to form a battery core, the electrolyte is injected into the battery core, and the battery is prepared through vacuum packaging, standing and formation processes.

[0094] Example 2

[0095] The difference between this embodiment and embodiment 1 is that the mass ratio of the polymer powder to the single crystal lithium manganese oxide is different.

[0096] Preparation of positive electrode materials:

[0097] S1. Mixing single crystal lithium manganese oxide and polymer powder to prepare a mixture.

[0098] The polymer powder is polytetrafluoroethylene (PTFE) powder; and the mass ratio of the polymer powder to single crystal lithium manganese oxide is 10000 ppm.

[0099] S2. The mixed material is placed in a jet mill for processing to obtain an intermediate.

[0100] Among them, the feeding frequency of the air jet mill is 10Hz, the classification frequency is 25Hz, and the fan frequency is 45Hz.

[0101] S3. Under the protection of an inert gas, the intermediate is subjected to high-temperature treatment to obtain a lithium manganese oxide material having a surface coated with a carbon layer, i.e., a positive electrode material.

[0102] The inert gas is argon, the high temperature treatment temperature is 400°C, the high temperature treatment time is 8 hours, and the thickness of the carbon layer is 25 nm.

[0103] Positive electrode: The positive electrode slurry (the mass ratio of the positive electrode material, binder (PVDF) and conductive agent (super-P) prepared above is 95:3:2) is coated on aluminum foil, dried and roll-pressed to obtain the positive electrode.

[0104] Negative electrode: The negative electrode slurry (the mass ratio of graphite, binder (CMC+SBR) and conductive agent (super-P) is 95:3:2) is coated on copper foil, dried and roll-pressed to obtain the negative electrode.

[0105] The mass ratio of electrolyte: ethylene carbonate (EC): propylene carbonate (PC): diethyl carbonate (DEC): lithium hexafluorophosphate (LiPF6) is 35:28:23:14.

[0106] Diaphragm (PE film, homemade).

[0107] Preparation of batteries

[0108] The positive electrode, the negative electrode and the separator are wound / stacked to form a battery core, the electrolyte is injected into the battery core, and the battery is prepared through vacuum packaging, standing and formation processes.

[0109] Example 3

[0110] The difference between this embodiment and embodiment 1 is that the mass ratio of the polymer powder to the single crystal lithium manganese oxide is different.

[0111] Preparation of positive electrode materials:

[0112] S1. Mixing single crystal lithium manganese oxide and polymer powder to prepare a mixture.

[0113] The polymer powder is polytetrafluoroethylene (PTFE) powder; and the mass ratio of the polymer powder to single crystal lithium manganese oxide is 500 ppm.

[0114] S2. The mixed material is placed in a jet mill for processing to obtain an intermediate.

[0115] Among them, the feeding frequency of the air jet mill is 10Hz, the classification frequency is 25Hz, and the fan frequency is 45Hz.

[0116] S3. Under the protection of an inert gas, the intermediate is subjected to high-temperature treatment to obtain a lithium manganese oxide material having a surface coated with a carbon layer, i.e., a positive electrode material.

[0117] The inert gas is argon, the high temperature treatment temperature is 400°C, the high temperature treatment time is 8 hours, and the thickness of the carbon layer is 1.25nm.

[0118] Positive electrode: The positive electrode slurry (the mass ratio of the positive electrode material, binder (PVDF) and conductive agent (super-P) prepared above is 95:3:2) is coated on aluminum foil, dried and roll-pressed to obtain the positive electrode.

[0119] Negative electrode: The negative electrode slurry (the mass ratio of graphite, binder (CMC+SBR) and conductive agent (super-P) is 95:3:2) is coated on copper foil, dried and roll-pressed to obtain the negative electrode.

[0120] The mass ratio of electrolyte: ethylene carbonate (EC): propylene carbonate (PC): diethyl carbonate (DEC): lithium hexafluorophosphate (LiPF6) is 35:28:23:14.

[0121] Diaphragm (PE film, homemade).

[0122] Preparation of batteries

[0123] The positive electrode, the negative electrode and the separator are wound / stacked to form a battery core, the electrolyte is injected into the battery core, and the battery is prepared through vacuum packaging, standing and formation processes.

[0124] Example 4

[0125] The difference between this embodiment and embodiment 1 is that the mass ratio of the polymer powder to the single crystal lithium manganese oxide is different.

[0126] Preparation of positive electrode materials:

[0127] S1. Mixing single crystal lithium manganese oxide and polymer powder to prepare a mixture.

[0128] The polymer powder is polytetrafluoroethylene (PTFE) powder; and the mass ratio of the polymer powder to single crystal lithium manganese oxide is 3000ppm.

[0129] S2. The mixed material is placed in a jet mill for processing to obtain an intermediate.

[0130] Among them, the feeding frequency of the air jet mill is 10Hz, the classification frequency is 25Hz, and the fan frequency is 45Hz.

[0131] S3. Under the protection of an inert gas, the intermediate is subjected to high-temperature treatment to obtain a lithium manganese oxide material having a surface coated with a carbon layer, i.e., a positive electrode material.

[0132] The inert gas is argon, the high temperature treatment temperature is 400°C, the high temperature treatment time is 8 hours, and the thickness of the carbon layer is 7.5 nm.

[0133] Positive electrode: The positive electrode slurry (the mass ratio of the positive electrode material, binder (PVDF) and conductive agent (super-P) prepared above is 95:3:2) is coated on aluminum foil, dried and roll-pressed to obtain the positive electrode.

[0134] Negative electrode: The negative electrode slurry (the mass ratio of graphite, binder (CMC+SBR) and conductive agent (super-P) is 95:3:2) is coated on copper foil, dried and roll-pressed to obtain the negative electrode.

[0135] The mass ratio of electrolyte: ethylene carbonate (EC): propylene carbonate (PC): diethyl carbonate (DEC): lithium hexafluorophosphate (LiPF6) is 35:28:23:14.

[0136] Diaphragm (PE film, homemade).

[0137] Preparation of batteries

[0138] The positive electrode, the negative electrode and the separator are wound / stacked to form a battery core, the electrolyte is injected into the battery core, and the battery is prepared through vacuum packaging, standing and formation processes.

[0139] Example 5

[0140] The difference between this embodiment and embodiment 1 is that the type of polymer is different; the time of high temperature treatment is different.

[0141] Preparation of positive electrode materials:

[0142] S1. Mixing single crystal lithium manganese oxide and polymer powder to prepare a mixture.

[0143] The polymer powder is polyvinylidene fluoride (PVDF) powder; and the mass ratio of the polymer powder to single crystal lithium manganese oxide is 2000ppm.

[0144] S2. The mixed material is placed in a jet mill for processing to obtain an intermediate.

[0145] Among them, the feeding frequency of the air jet mill is 10Hz, the classification frequency is 25Hz, and the fan frequency is 45Hz.

[0146] S3. Under the protection of an inert gas, the intermediate is subjected to high-temperature treatment to obtain a lithium manganese oxide material having a surface coated with a carbon layer, i.e., a positive electrode material.

[0147] The inert gas is argon, the high temperature treatment temperature is 500°C, the high temperature treatment time is 6 hours, and the thickness of the carbon layer is 6 nm.

[0148] Positive electrode: The positive electrode slurry (the mass ratio of the positive electrode material, binder (PVDF) and conductive agent (super-P) prepared above is 95:3:2) is coated on aluminum foil, dried and roll-pressed to obtain the positive electrode.

[0149] Negative electrode: The negative electrode slurry (the mass ratio of graphite, binder (CMC+SBR) and conductive agent (super-P) is 95:3:2) is coated on copper foil, dried and roll-pressed to obtain the negative electrode.

[0150] The mass ratio of electrolyte: ethylene carbonate (EC): propylene carbonate (PC): diethyl carbonate (DEC): lithium hexafluorophosphate (LiPF6) is 35:28:23:14.

[0151] Diaphragm (PE film, homemade).

[0152] Preparation of batteries

[0153] The positive electrode, the negative electrode and the separator are wound / stacked to form a battery core, the electrolyte is injected into the battery core, and the battery is prepared through vacuum packaging, standing and formation processes.

[0154] Comparative Example 1

[0155] The difference between this comparative example and Example 1 is that the single crystal lithium manganese oxide material is not coated.

[0156] Positive electrode: The positive electrode slurry (the mass ratio of single crystal lithium manganese oxide, binder (PVDF) and conductive agent (super-P) is 95:3:2) is coated on aluminum foil, dried and roll-pressed to obtain the positive electrode.

[0157] Negative electrode: The negative electrode slurry (the mass ratio of graphite, binder (CMC+SBR) and conductive agent (super-P) is 95:3:2) is coated on copper foil, dried and roll-pressed to obtain the negative electrode.

[0158] The mass ratio of electrolyte: ethylene carbonate (EC): propylene carbonate (PC): diethyl carbonate (DEC): lithium hexafluorophosphate (LiPF6) is 35:28:23:14.

[0159] Diaphragm (PE film, homemade).

[0160] Preparation of batteries

[0161] The positive electrode, the negative electrode and the separator are wound / stacked to form a battery core, the electrolyte is injected into the battery core, and the battery is prepared through vacuum packaging, standing and formation processes.

[0162] Comparative Example 2

[0163] The single crystal lithium manganate material of the same mass as that in Example 1 was added into the sucrose solution, dried, and then calcined at 600° C. for 8 h to obtain the positive electrode material.

[0164] Positive electrode: The positive electrode slurry (the mass ratio of the positive electrode material, binder (PVDF) and conductive agent (super-P) prepared above is 95:3:2) is coated on aluminum foil, dried and roll-pressed to obtain the positive electrode.

[0165] Negative electrode: The negative electrode slurry (the mass ratio of graphite, binder (CMC+SBR) and conductive agent (super-P) is 95:3:2) is coated on copper foil, dried and roll-pressed to obtain the negative electrode.

[0166] The mass ratio of electrolyte: ethylene carbonate (EC): propylene carbonate (PC): diethyl carbonate (DEC): lithium hexafluorophosphate (LiPF6) is 35:28:23:14.

[0167] Diaphragm (PE film, homemade).

[0168] Preparation of batteries

[0169] The positive electrode, the negative electrode and the separator are wound / stacked to form a battery core, the electrolyte is injected into the battery core, and the battery is prepared through vacuum packaging, standing and formation processes.

[0170] The test parameters of the embodiments and comparative examples are summarized in Table 1 below:

[0171] Test Case

[0172] (1) Thickness test

[0173] (2) Cycle test

[0174] The battery cell was transferred to a 25°C constant temperature box for charge and discharge cycle test. The charge and discharge test steps were as follows: 1) 0.33C constant current discharge to 3.5V; 2) 0.33C constant current constant voltage charge to 4.9V (cut-off current 0.05C); 3) 0.33C rate constant current discharge to 3.5V. The cycle test results are shown in Table 2.

[0175] (3) Battery internal resistance test

[0176] (4) Transition metal element dissolution test

[0177] The cycled battery was disassembled, the negative electrode was taken out, and the negative electrode was completely oxidized and blackened in the external environment. It was then soaked in DMC for 24 hours and then scraped for powder treatment. The powder material was washed, filtered, dried, and ground, and sent to the inductively coupled plasma atomic emission spectrometer ICP to analyze the relative content of Mn in the sample. The test results are shown in Table 2.

[0178]

[0179] As can be seen from the above table, the concentration of manganese ions on the negative electrode side of the positive electrode material prepared by the preparation process of this application is greatly reduced, and it can be seen that the coating layer has a good barrier effect on manganese ions. The possible reason is that through the preparation process of this application, a uniform and continuous coating layer is formed on the surface of the single crystal lithium manganese oxide, achieving good coating of the single crystal lithium manganese oxide. The above is only a speculation on the possible mechanism of this application and does not constitute a limitation on the scope of protection of this application.

[0180] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0181] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.

Claims

1. A method for preparing a positive electrode material, characterized in that: The following steps are involved: S1, mixing single crystal lithium manganese oxide and polymer powder to prepare a mixture; S2, placing the mixed material into a jet mill for processing to obtain an intermediate; S3, under the protection of an inert gas, subjecting the intermediate to a high-temperature treatment to obtain a lithium manganese oxide material having a surface coated with a carbon layer, i.e., a positive electrode material; Wherein, the polymer powder is a fiberizable polymer powder; The temperature of the high temperature treatment is T1, the carbonization temperature of the polymer powder is T2, and T1≥T2.

2. The method for preparing the positive electrode material according to claim 1, characterized in that: The polymer powder includes at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene (PE), and polypropylene (PP).

3. The method for preparing the positive electrode material according to claim 1, characterized in that: In the mixture, the mass ratio of the polymer powder to the single crystal lithium manganese oxide is 500ppm to 10000ppm; Preferably, in the mixture, the mass ratio of the polymer powder to the single crystal lithium manganese oxide is 2000ppm to 3000ppm.

4. The method for preparing the positive electrode material according to claim 1, characterized in that: The feeding frequency of the jet mill is 8 Hz to 12 Hz; and / or the classification frequency of the jet mill is 20 Hz to 30 Hz; And / or the fan frequency of the jet mill is 40Hz-50Hz.

5. The method for preparing the positive electrode material according to claim 1, characterized in that: The high temperature treatment time is 6h to 10h.

6. The method for preparing the positive electrode material according to claim 1, characterized in that: The inert gas is at least one of nitrogen, helium and argon.

7. The method for preparing the positive electrode material according to claim 1, characterized in that: The thickness of the carbon layer is 1 nm to 30 nm.

8. A positive electrode, characterized in that It includes a positive electrode material prepared by the method for preparing a positive electrode material according to any one of claims 1 to 7.

9. The positive electrode according to claim 8, characterized in that The positive electrode further includes a binder and a conductive agent.

10. A battery, characterized in that: Comprising the positive electrode as claimed in claim 8 or 9.